2009
DOI: 10.1152/ajpheart.00693.2008
|View full text |Cite
|
Sign up to set email alerts
|

Longevity is associated with increased vascular resistance to high glucose-induced oxidative stress and inflammatory gene expression in Peromyscus leucopus

Abstract: Labinskyy N, Mukhopadhyay P, Toth J, Szalai G, Veres M, Losonczy G, Pinto JT, Pacher P, Ballabh P, Podlutsky A, Austad SN, Csiszar A, Ungvari Z. Longevity is associated with increased vascular resistance to high glucose-induced oxidative stress and inflammatory gene expression in Peromyscus leucopus. Am J Physiol Heart Circ Physiol 296: H946 -H956, 2009. First published January 30, 2009 doi:10.1152/ajpheart.00693.2008.-Vascular aging is characterized by increased oxidative stress and proinflammatory phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 62 publications
2
45
0
Order By: Relevance
“…Our data showing reduced production of H 2 O 2 and O 2 ·Ϫ in skeletal muscle mitochondria are consistent with previous studies from other tissues in P. leucopus (12,21,39,66). In the brain, heart, and endothelial cells of P. leucopus, investigators demonstrate a low rate of mitochondrial O 2 ·Ϫ and H 2 O 2 generation (39,58), high activities of catalase and glutathione peroxidase (21,58), low levels of oxidative damage to proteins (32,58), delayed accumulation of DNA damage (62), and enhanced resistance to oxidative stress in vitro (21,66) compared with M. musculus.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data showing reduced production of H 2 O 2 and O 2 ·Ϫ in skeletal muscle mitochondria are consistent with previous studies from other tissues in P. leucopus (12,21,39,66). In the brain, heart, and endothelial cells of P. leucopus, investigators demonstrate a low rate of mitochondrial O 2 ·Ϫ and H 2 O 2 generation (39,58), high activities of catalase and glutathione peroxidase (21,58), low levels of oxidative damage to proteins (32,58), delayed accumulation of DNA damage (62), and enhanced resistance to oxidative stress in vitro (21,66) compared with M. musculus.…”
Section: Discussionsupporting
confidence: 93%
“…In the brain, heart, and endothelial cells of P. leucopus, investigators demonstrate a low rate of mitochondrial O 2 ·Ϫ and H 2 O 2 generation (39,58), high activities of catalase and glutathione peroxidase (21,58), low levels of oxidative damage to proteins (32,58), delayed accumulation of DNA damage (62), and enhanced resistance to oxidative stress in vitro (21,66) compared with M. musculus. Interestingly, we found that the levels of H 2 O 2 and O 2 ·Ϫ are lower, even when inhibitors (rotenone or antimycin A) were added to stimulate their maximal production.…”
Section: Discussionmentioning
confidence: 99%
“…3) (8, 18, 56). The intimate link among aging, Nrf2 activation, and vascular health is also underscored by the observations that arteries of extremely longlived muroid rodents (P. leucopus, maximal lifespan: ϳ8 years) exhibit an increased expression of Nrf2-driven antioxidant enzymes, decreased cellular and mitochondrial levels of ROS, and increased resistance to the proinflammatory and proapoptotic effects of hyperglycemia compared with vessels of shorter-lived M. musculus (13,33,50,54).…”
Section: Discussionmentioning
confidence: 99%
“…Aorta segments isolated from young and aged rats were maintained in organoid culture (for 24 h) as previously described (60). Vessels were treated with H 2O2 (from 10 Ϫ6 to 10 Ϫ4 mol/l) or high glucose (30 mmol/l), which effectively increases mitochondrial H2O2 generation (33). At the end of the culture period nuclear Nrf2 binding activity, expression of Nrf2 targets, production of ROS, and apoptotic cell death were assayed as described below.…”
Section: Methodsmentioning
confidence: 99%
“…The lower AI/AG as well as the slower increase of plasma glucose level after F/R meal than that after M/R meal implied that the Caspian Sea Yogurt would increase insulin efficiency. Remarkable characteristics of the Caspian Sea Yogurt consumption before complex carbohydrate intake such as lower AI/AG and peak delay in postprandial glucose level would play an important role for prevention of vascular aging caused by high glucose induced oxidative stress (Labinskyy et al, 2009). Furthermore, slow rise of postprandial glucose level may be beneficial on vascular endothelial cells, since intermittent high glucose rather than constant high glucose was revealed to enhance reactive oxygen species-induced apoptosis in human umbilical vein endothelial cells (Risso et al, 2001, Quagliaro et al, 2003.…”
Section: Potential Benefit Of Caspian Sea Yogurtmentioning
confidence: 99%